Perhitungan Ulang Chassis Mobil Marapi Evo 1 Untuk Kontes Mobil Hemat Energi 2021 - Nurul Izza; Yuli Yetri (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
In 2021 the Padang State Polytechnic Marapi team participated in an energy-efficient car contest held by PUSPRESNAS. The Marapi team participated in the diesel engine prototype category which was held at the State University of Surabaya, East Java. To keep the efficiency of the car increasing, a stable and lightweight chassis is needed. The Marapi Evo 1 uses a ladder frame type chassis with an overall length of 2000mm and hollow aluminum material. The chassis is designed to withstand a load of more than 200kg. In this journal, calculations will be carried out regarding the distribution of forces acting on the Marapi Evo 1 car chassis when accelerating. There are three testing methods, namely Finite Element Method (FEM) Testing Using ANSYS, Force Distribution Analysis, and Total Traction Analysis. From the results of the analysis and calculations that have been carried out, it can be concluded that the Marapi Evo 1 chassis is feasible and safe to compete in the 2021 Energy Saving Car Contest. In addition, a total traction force of 330.216925 N which states that the Marapi Evo 1 car is capable of maneuvering very well when there is a change of speed.